DETERMINATION OF THE PARAMETERS OF PERIODIC ON / OFF MATERIALIZED VIEW IN THE INFORMATION SYSTEM - Кунгурцев, Алексей Борисович; Возовиков, Юрий Николаевич; Винь, Нгуен Чан Куок (Eastern-European Journal of Enterprise Technologies, 2012)
A method for analyze the sequence of requests with the purpose to identify the IS parameters needed to control the periodic enabling and disabling materialized views (MV) is proposed it this article.